Rusové pohledem pražské středoškolské mládeže - Šmídová, Michaela (Lidé města, 2000)
The conducted research has revealed that the attitude of respondents (students of Prague secondary schools) to Russians certainly cannot be called unambiguous. Its ambiguousness is confirmed by evident ambivalence which appeared among individual respondents as well as various groups of problems. One and the same respondent can display good knowledge of Russian culture, but can be at the same time afraid of Russians and assume a less tolerant position to them. One the one hand, there is the look at Russians in Russia (admiration of the Russians' ability to survive everything) and at Russians as immigrants in the Czech Republic on the other (one-sidedness and oversimplification in the respondents' views). In general it can be said that apart from a few exceptions the respondents' attitudes to Russians do not reflect any indifference, let alone antipathy. From this point of view, the students are representatives of a new generation which is not burdened with past controversial events in Czech-Russian relations, although they know about them and bear them in mind. One can record among most respondents fairly realistic attitudes concerning both Czech-Russian political relations and the closeness of Russians and Czechs as Slavs. However, the above-mentioned realism is also confronted with some stereotypes which appear if there is a lack of doser experience or deeper knowledge.